Culture and characterisation of canine mitral valve interstitial and endothelial cells. Issue 1 (April 2015) - Liu, M.-M.; Flanagan, T.C.; Lu, C.-C.; French, A.T.; Argyle, D.J.; Corcoran, B.M.
Highlights Successful culture and characterisation of valve interstitial and endothelial cells. Identification of CD31 expression and Dil-Ac-LDL uptake as the prime markers for differentiating VECs from VICs. A specific endothelial culture medium for primary VEC cultures enhanced the endothelial properties of the cells.